2008
DOI: 10.1021/la801817e
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Composite Films Produced on Various Substrates

Abstract: Hydrophilic silica (SiO2) nanoparticles were dispersed in solutions of poly(methyl methacrylate) (PMMA) and in solutions of a commercial poly(alkyl siloxane) (Rhodorsil 224), and the suspensions were sprayed on glass surfaces. The effect of the particle concentration on the hydrophobic character of PMMA-SiO2 and Rhodorsil-SiO2 films was investigated and showed the following: (i) Static contact angles (theta s), measured on surfaces that were prepared from dilute dispersions (particle concentration <1% w/v), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
206
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(229 citation statements)
references
References 38 publications
19
206
0
4
Order By: Relevance
“…By comparing CA values obtained in samples treated with UCA-T and UCA-TS, similar values are obtained, showing a slight increase for the gel containing silica nanoparticles. This can be related to the increase in roughness produced by particles in the surface of the stone [13,33]. Table S1 show water droplet static and dynamic contact angle (CA) values.…”
Section: Evaluation Of the Effectiveness On Quarry Stonementioning
confidence: 97%
See 2 more Smart Citations
“…By comparing CA values obtained in samples treated with UCA-T and UCA-TS, similar values are obtained, showing a slight increase for the gel containing silica nanoparticles. This can be related to the increase in roughness produced by particles in the surface of the stone [13,33]. Table S1 show water droplet static and dynamic contact angle (CA) values.…”
Section: Evaluation Of the Effectiveness On Quarry Stonementioning
confidence: 97%
“…However, this change does not produce modifications in repellence behavior because the original topography of the stone surface is hardly modified by the coating (see Figure 4). Consequently, as the biocalcareous stone is a high porosity material composed of macropores with distance between roughness peaks in the micrometer range, and a significantly lower distance between roughness peaks in the nanometer range is required to produce a Cassie-Baxter regime [13,33,47]. The coating containing nanoparticles (UCA-TS) cannot produce a repellent surface on which the water droplets do not stick [48].…”
Section: Evaluation Of the Effectiveness On Quarry Stonementioning
confidence: 99%
See 1 more Smart Citation
“…Hou and Wang [73] prepared superhydrophobic polystyrene/titania nanocomposites with superhydrophilic property under UV irradiation. It is postulated that for a particular combination of metal oxide-polymer film, the superhydrophobicity of the composite material is independent of type of the metal oxide used and substrate properties [74]. Sometimes during the photocatalytic process of TiO 2 , the polymer matrix is degraded.…”
Section: Metal Oxide-polymer Nanocomposite Filmsmentioning
confidence: 99%
“…Numerous methods, including photolithography [6], plasma treatment [7], templates [8], chemical deposition [9], solgel processes [10], chemical vapor deposition (CVD) [11], casting, and chemical etching [12], have been utilized to fabricate superhydrophobic surfaces. Several studies have been reported on using polymers and polymer nanocomposites for various applications such as fabricating hydrophobic/superhydrophobic surfaces [13][14][15][16][17][18][19][20][21]. Therefore, development of hydrophobic/superhydrophobic polymers and polymer nanocomposites has become an interesting subject in materials science.…”
mentioning
confidence: 99%